Penerapan Nilai-Nilai Religius Santri Melalui Program Tahfidz Menginap di Rumah Qur’an - Nur Aidila Fitria; Muhammad Yoga Julyanur; Eko Nursalim (STIT Syekh Muhammad Nafis Tabalong, 2023)
The world of education today, especially Qur'anic education, has many challenges. This can be seen from children's excessive obsession with gadgets that make their religious character seem to be eroded by the sophistication of the times marked by the rapid advancement of information and technology. Therefore, it is important to know that instilling religious values early on in children is very important. This research uses a descriptive type qualitative approach by collecting data through an unstructured interview process. This study aims to analyze how the application of religious values through the